Translating Project Achievements into Strategic Plans: A Case Study in Utilization-Focused Evaluation - Ramírez, Ricardo; Kora, Galin; Brodhead, Dal (Journal of MultiDisciplinary Evaluation, 2017)
Background: Utilization-focused evaluation (UFE) is a decision-making framework intended to design and implement evaluations that get utilized. In this case study, the UFE approach was applied to the evaluation of a youth training and employment program in Kenya. Purpose: Analyze a case study based on empirical experience with the lens of evaluation use and influence. Setting: Nairobi and other urban and peri-urban settings, Kenya. Intervention: The evaluation of a youth training and employment program that provided direct training for marginalized youth as well as capacity building for employment and adapted a Basic Employability Skills Training (BEST) model from India. Research design: Analysis of a case study to describe: how the evaluation approach provided enabling factors for funders and grantees to turn evaluation into a learning intervention; the benefit of clarifying a project’s theory of change; and learning how to combine summative and developmental evaluation. Data collection and analysis: A case study based on an evaluation consultancy. The evaluation included site visits, extensive documentation review, qualitative and quantitative data collection. Findings: The ‘facilitation of use’ (a step in UFE) provided a bridge between a summative and a developmental evaluation. The evaluators and program partners developed a learning relationship wherein the evidence influenced the subsequent project design and strategy.